Assessment of Green Open Space in the Transit-Oriented Development Area in Jakarta - Endangsih, T. (Horizon Research Publishing, 2022)
The Jatinegara Station area has developed as a commercial area causing the surrounding residential areas to develop into dense settlements and have limitations in providing facilities and infrastructure, especially green open spaces. Along with the increasing intensity of commercial activities, this has an impact on changing green open spaces into built-up land. The purpose of this study was to examine the existing condition of green open space in the Jatinegara TOD area and then compare it with the standards set by the local government. The results of this comparison are used to provide input on the design of green open spaces in the research area. This goal is achieved by using a quantitative approach. The analysis of the need for green open space is calculated based on the standard of 30% of the total area. The need for green open space is 20 m2 per person and the Gerarchis method is used to calculate the need for green space based on oxygen demand. The analytical method used in this research is descriptive quantitative analysis. As the first step is to identify the characteristics of green open space, analyze the availability of green open space and its form and typology. Based on the results of the study, it can be concluded that the availability of green open space affects the environmental quality of the TOD area. The form and typology of green open spaces found in the study area are urban forest green open spaces and sub-district environmental parks. Therefore, the existence of green open spaces needs to be maintained through the development and arrangement of green open spaces by taking into account the types of vegetation that can absorb CO2.